Depositional history and provenance of cratonic "Purana" basins in southern India: A multipronged geochronology approach to the Proterozoic Kaladgi and Bhima basins. (21st December 2018) - Joy, Sojen; Patranabis‐Deb, Sarbani; Saha, Dilip; Jelsma, Hielke; Maas, Roland; Söderlund, Ulf; Tappe, Sebastian; van der Linde, Gert; Banerjee, Amlan; Krishnan, Unni
Abstract : Peninsular India is a collage of Archaean cratonic domains separated by Proterozoic mobile belts. A number of cratonic basins, known as "Purana basins" in the Indian literature, formed in different parts of the Indian Peninsula during extensional tectonic events, from Paleoproterozoic through Neoproterozoic times. In this contribution, we present a diversity of new geochronological data for different units within the Kaladgi and the Bhima basins, which overlie the western and eastern Dharwar cratons, respectively. The new geochronology data are discussed in terms of depositional history and provenance of these poorly understood Proterozoic intracratonic basins. For the Kaladgi Group, a U–Pb baddeleyite age of 1, 861 ± 4 Ma obtained for a dolerite dyke intruding the Yendigere Formation is used to constrain the minimum age of deposition of the lower Kaladgi Group. This result demonstrates that this part of the succession is comparable in age to the Papaghni Group of the Cuddapah Basin, heralding onset of Purana sedimentation at 1, 900 Ma. The detrital zircon populations from the clastic rocks of the Kaladgi and Bhima basins show unique and distinct age patterns indicating different source of sediments for these two basins. Palaeocurrent analysis indicates a change in provenance from south or southeast to west or northwest between the Kaladgi and Bhima clastic sedimentation. New U–Th–Pb and Rb–Sr radiometric dates of limestones and glauconite‐bearing sandstones of the Bhima Group (Bhima Basin) and the Badami Group (Kaladgi Basin) indicate deposition at around 800–900 Ma, suggesting contemporaneity for the two successions. Thus, the unconformity between the Kaladgi Group and the overlying Badami Group represents a time gap of up to 1, 000 Myr. These new results demonstrate the complex multistage burial and unroofing history of the Archaean Dharwar Craton throughout the Proterozoic, with important implications for exploration of metal deposits and diamonds in Peninsular India.